MESALAZINE PREFORMULATION AND SOLUBILITY STUDY - HAMEED, RUSSUL; GHAREEB, MOWAFAQ M. (International Journal of Applied Pharmaceutics, 2026)
Objective: Aim of preformulation study is to develop the elegant, stable, effective and safe dosage form by assay solubility and stability study of MSL. Methods: Preformulation study was done to check the purity and stability of drug by different steps of preformulation study, first of this step involve identification of melting point by DSC, and by using UV spectrophotometry can be detection of lambda max and calibration curve in ethanol and phosphate buffer pH7.4. Drug was dissolved in different media to evaluate its solubility and stability in The study includes solubility, stability, and pH of drug in different oil (Almond oil, Grape oil, Sesame oil, Clove oil, Olive oil, Jojoba oil, and Labrafil oil), different surfactants (Cremophor, Tween 40, Tween 80, PEG 400, PEG600, PEG200, Labrasol), different co surfactants (Oleic acid, Imm 948, Vitamin E, frankincense oil, Labrafac oil, and Imwitor30 with and without different antioxidants (sodium thiosulfate, sodium metabisulfite, vitamin C, and Vitamin E. FTIR done to check purity and identity of drug and to evaluate MSL-solubilizing media interaction. Results: The results from the Preformulation studies show melting point and lambda max of mesalamine were found to be 285.5 °C and 330 nm respectively. MSL best condition of preparing in a solution in oil and acidic media at room temperature. The FTIR study of pure MSL confirms the purity of drug and FTIR show the interaction of drug with tween 40; in which FTIR of MSL-tween40 show chemical interaction. Conclusion: from solubility study of MSL in deferent media show different concentration of drug dissolve in mg/ml and stability of drug was affected by type of media mainly pH of media in which oil media show better stability.